RADIKALISME DALAM PANDANGAN ISLAM (Analisa dalam Perspektif al Qur’an dan Hadits) - Muhammad Qomarullah (El-Ghiroh : Jurnal Studi Keislaman, 2016)
Islam is a religion that was revealed to the Prophet Muhammad as the last prophet and messenger for a way of life of all mankind until the end of time. Understanding Islam harfiyah means" peaceful, happy, bow, and clean". From the definition of Islam is that it does not justify the concept of radicalism and fanaticism that lead to acts of violence or terrorism. Lately reappeared fanaticism and religious radicalism in Indonesia, even rare due to narrow thinking that there was a problem that the use of violence in addressing the differences. The factors the occurrence of radicalism is faaktor thought, economic, political, social, psychological and educational.